Impact of online training for capacity building on adolescent health among health care providers of residential schools: a quasi-experimental study - Sathiyamoorthi, Sathiyanarayanan; Aravindakshan, Rajeev; Avula, Vijaya Chandra Reddy; Sharmila, Vijayan; Naidu, Navya Krishna; Dhinakaran, Hashini (International Journal Of Community Medicine And Public Health, 2025)
Background: Adolescence is a critical period of growth and development. Despite the increasing focus on adolescent health, gaps in knowledge and skills among healthcare providers in residential schools can hinder effective adolescent healthcare delivery. To evaluate the impact of an online training program on capacity building for adolescent health among healthcare providers in residential schools using a pretest-posttest design. Methods: A six-week structured online training program covering key aspects of adolescent health, including management of dermatological, reproductive, ear nose throat, the common mental health issues were conducted by subject experts among healthcare providers from residential schools. A pretest-posttest study design was employed to assess the effectiveness of online training. Paired t-tests were used to compare pretest and post-test scores, and Cohen’s D was calculated for measuring effect size. Results: About 214 healthcare providers attended the training program, out of which 82 (38.3%) were males and 134 (62.7%) were females. In dermatology, the mean pretest score was 4.214, which increased to 6.524 in the post-test, reflecting a 54.82% improvement. The highest percentage improvement was observed in ENT (64.71%). The paired t-test analysis revealed a statistically significant improvement in knowledge across all domains following the online training program. Effect size calculations (Cohen’s d) demonstrated a very large effect for dermatology (d=2.66), psychiatry (d=2.58), and mental health (d=2.46), suggesting a strong impact of the training on these topics. Conclusion: The findings suggest that online training is an effective tool for enhancing the knowledge and skills of healthcare providers in residential schools.